The Element of Al-Dakhil in The Shia Interpretation of Imamah: A Comparative Study of The Interpretations of Fath Al-Qadir and Majma' Al-Bayan - Qurani, Hizbia; Riyadi, Abdul Qadir (QiST: Journal of Quran and Tafseer Studies, 2026)
This article examines the element of al-dakhil in the interpretation of verses about Imāmah in QS. al-Baqarah: 124, QS. al-Ma'idah: 55–56, and Surah al-Ma'idah: 67 in Fath al-Qadir by al-Shawkani and Majma' al-Bayan by al-Ṭabrisī. The research questions are: (1) What is the concept of Imamah in Shi'ism? (2) How does the element of al-dakhil operate in the interpretation of these verses, and (3) What are the differences between the two interpretations? Based on the results of this comparative study, we will see the extent to which the mufasir's theological background can influence the construction of meaning. This study aims to identify the form and operational mechanism of al-dakhil in both interpretations. The study uses a qualitative approach based on a literature review with a comparative interpretation method (tafsir muqaran). The analysis is conducted through the identification of interpretations, tracing the history used, and testing ideological tendencies in the framing of meaning. The results show that in Majma' al-Bayan, the element of al-dakhil appears through a doctrinal framing that is consistent with Imamiyah theology and the selection of history that supports the concept of divine leadership and the infallibility of the imam. Conversely, in Fath al-Qadir, this element is relatively minimal because al-Shawkani emphasizes the validity of sanad and more general contextual meanings without explicitly linking them to specific doctrines. This study contributes by positioning al-dakhil as an analytical category for reading ideological influences in tafsir and enriching comparative tafsir studies in understanding the relationship between text, tafsir, and theological affiliation.